Disadvantage across the Generations: What Do We Know about Social and Economic Mobility in Australia? - Cobb-Clark, Deborah (My University, 2010)
This paper begins by considering the Australian evidence on intergenerational social and economic mobility in the context of the international literature. Recent evidence from the Youth in Focus project is used to highlight the effects of growing up in socio-economic disadvantage on a range of outcomes for young Australians.
Economic Record
Keywords: Disadvantage; Intergenerational Transfer; Intergenerational transfer; Intergenerational Transfer; Disadvantage; Intergenerational transfer